1987
DOI: 10.1111/j.1600-0765.1987.tb01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized dental plaque is mitogenic for nylon wool‐purified human cord blood T lymphocytes

Abstract: Solubilized dental plaque is mitogenic for nylon woolpurified human cord blood T lymphocytes. Journal of Periodontal Research 1987; 22:94-102. Human cord blood T lymphocytes were purified by filtration through nylon wool columns and tested for their ability to synthesize DNA in response to stimulation with solubilized dental plaque, phytohemagglutinin and streptolysin O. Ninety out of 106 cord blood T lymphocyte preparations (85%) responded significantly (p<0.05) to solubilized dental plaque. DNA synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(29 reference statements)
0
1
1
Order By: Relevance
“…Baker & Tondreau (12) reported that solubilized dental plaque is mitogenic for puri®ed T lymphocytes, however in this study sonic extracts of A. actinomycetemcomitans and E. coli LPS did not stimulate puri®ed T cells to produce IFN-g directly. This evidence indicated that accessory cells were needed for this reaction.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Baker & Tondreau (12) reported that solubilized dental plaque is mitogenic for puri®ed T lymphocytes, however in this study sonic extracts of A. actinomycetemcomitans and E. coli LPS did not stimulate puri®ed T cells to produce IFN-g directly. This evidence indicated that accessory cells were needed for this reaction.…”
Section: Discussioncontrasting
confidence: 75%
“…gingivalis FDC 381, A. actinomycetemcomitans FDC Y4 and B. forsythus were used in the study. The sonicated extracts of these bacteria were prepared as described previously (12). In brief, cultured bacterial cells on ice were sonicated (150 W) for 2 min and then suspended in distilled water.…”
Section: Bacterial Preparationmentioning
confidence: 99%